2016
DOI: 10.1093/ndt/gfv423
|View full text |Cite
|
Sign up to set email alerts
|

Selective screening for distal renal tubular acidosis in recurrent kidney stone formers: initial experience and comparison of the simultaneous furosemide and fludrocortisone test with the short ammonium chloride test

Abstract: The F+F test is characterized by an excellent sensitivity and negative predictive value, and the diagnosis of incomplete dRTA can be excluded reliably in a patient who acidifies their urine normally with this test. However, its lack of specificity is a drawback, and if there is any doubt, an abnormal F+F test may need to be confirmed by a follow-up NHCl test. Ideally, a prospective blinded study in unselected KSFs is needed to accurately assess the reliability of the F+F test in diagnosing, rather than excludi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
13
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
3
13
1
2
Order By: Relevance
“…Consistent with this performance is the F&F test's relative failure to cause the acidemia seen after NH 4 Cl, in fact leading to a small increase in venous pH and bicarbonate. This lack of specificity for diagnosing idRTA is similar to the results of another study, in which both tests were administered (8).…”
supporting
confidence: 86%
“…Consistent with this performance is the F&F test's relative failure to cause the acidemia seen after NH 4 Cl, in fact leading to a small increase in venous pH and bicarbonate. This lack of specificity for diagnosing idRTA is similar to the results of another study, in which both tests were administered (8).…”
supporting
confidence: 86%
“…All healthy probands were able to acidify their urine below pH 5.3 with the f+f test or the ammonium chloride test while urine pH of dRTA patients remained above pH 5.3 indicating defective urinary acidification. In a follow-up study the f+f test was further used in a preselected cohort of kidney stone formers[57]. In this study the authors confirmed a distinct sensitivity and excellent negative predictive value of this test to exclude incomplete dRTA in patients with kidney stones or nephrocalcinosis or both.…”
mentioning
confidence: 56%
“…By using the ammonium chloride test, the authors demonstrated that the test is a reliable method to evaluate the ability of the kidney to excrete acid. Recently the test has been applied in several human studies[56][57][58]. The f+f test has been tested in complete and incomplete dRTA and it is less specific than the gold standard ammonium chloride test.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to a PubMed search, the table lists chronologically series of 10 or more patients published in English urine sample after 12 h without eating and 8 h without drinking as a discriminating test to detect adults with urolithiasis in whom NH4Cl loading should be performed to confirm iDRTA. In general, it could be stated that a fasting urine pH appropriately acid, that is < 5.5, excludes the diagnosis iDRTA, whereas the finding of a less acid fasting urine pH requires the subsequent use of more aggressive tests to reach a diagnosis of iDRTA 22. As shown inTable 1, iDRTA has been found with high, but variable, frequency in entities such as nephrolithiasis, nephrocalcinosis, Sjögren disease, low bone mass and sickle-cell disease, as well as other interstitial nephropathies and autoimmune diseases.…”
mentioning
confidence: 99%